Synthesis and biocidal screening of 4-biphenyl acetamides derivatives. (International Journal of Emerging Trends in Science and Technology, 2017)
The present paper deals with the synthesis of 4-biphenyl acetic acid amides by condensation ofcorresponding acid chlorides with suitable amines. the structure of newly synthesized compounds wereelucidated on the basis of their IR, TLC and elemental analysis data. The compounds were also screenedfor their anti-bacterial and anti-fungal activity.